2017
DOI: 10.1186/s12906-017-1939-1
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of traditional Chinese medicine in patients with dysfunctional uterine bleeding in Taiwan: a nationwide population-based study

Abstract: BackgroundMany patients with gynecological disorders seek traditional medicine consultations in Asian countries. This study intended to investigate the utilization of traditional Chinese medicine (TCM) in patients with dysfunctional uterine bleeding (DUB) in Taiwan.MethodsWe analyzed a cohort of one million individuals randomly selected from the National Health Insurance Research Database in Taiwan. We included 46,337 subjects with newly diagnosed DUB (ICD-9-CM codes 626.8) from January 1, 1997 to December 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…We also observed that younger patients (18–39 y/o) and those who lived in more urbanized areas were relatively more likely to choose CM, in accordance with previous studies [ 38 , 39 ]. Patients younger than 40 years old are likely to be more aware of alternative therapeutic choices.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed that younger patients (18–39 y/o) and those who lived in more urbanized areas were relatively more likely to choose CM, in accordance with previous studies [ 38 , 39 ]. Patients younger than 40 years old are likely to be more aware of alternative therapeutic choices.…”
Section: Discussionsupporting
confidence: 92%
“…Glycerophospholipids are key components of the cells and are involved in metabolism and signaling. LysoPC(20:5) is lysophospholipid, which play an important role in lipid signal transduction by acting on the lysophosphatidic receptor (LPL-R) ( Lingwood and Simons, 2010 ). Previous studies based on metabolomics have demonstrated that the serum NMR-based metabolomics analysis method was sensitive enough to distinguish individuals having artificial abortions from healthy individuals and can provide a further understanding of the mechanism of artificial abortion complications ( Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qi stagnation usually suggests that energy and information cannot move smoothly to or from its appropriate location [ 29 ]. Xiang-Fu is used to treat qi stagnation, and Yi-Mu-Cao is used to treat blood stasis [ 34 ]. It has been used to treat dysmenorrhea and irregular menstruation [ 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%